Analisis Kompetensi Literasi Informasi dan Keterampilan Sosial terhadap Kinerja Pustakawan Perpustakaan Proklamator Bung Karno - Eka Urwanto (Universitas Islam Kadiri, 2020)
This research was conducted with the aim of (1) Knowing the effect of information literacy competence on the librarian performance of the Bung Karno Library, (2) Knowing the effect of social skills on the librarian performance of the Bung Karno Library, (3) Knowing the effect of information literacy competence and social skills on librarian performance. Bung Karno's Library. The research was conducted at UPT Bung Karno Blitar Library with a total sample of 31 librarian functional. To solve the problem formulation and achieve the objectives of this study, a correlation quantitative approach (Corelational Study) or causal associative is used. The results prove that the variables of information literacy competence and social skills simultaneously have a significant effect on librarian performance by testing the F test (Simultaneous) where F count 33.248> F table 3.33. However, partially, the information literacy competency variable has no significant effect on the librarian performance variable. with t-test (partial) shows that t count 0.739 < t table 2.048. For the social skills competency variable has a significant effect on librarian performance with the t-test (partial) showing that t count is 4.048> t table 2.048. Keywords: librarian, social skills, performance